Size and shape of polypyrrole particles in aqueous solutions of poly-( N-vinylpyrrolidone) - Ya. O. Mezhuev (Тонкие химические технологии, 2013)
Based on the IR spectroscopy data and on the analysis of rheological characteristics of polypyrrole aqueous suspension stabilized with poly-(N-vinylpyrrolidone) we conjecture that a physical lattice composed with poly-(N-vinylpyrrolidone) is formed, where the lattice points are the polypyrrole chain aggregates interlaced with poly-(N-vinylpyrrolidone) chains. It was shown that there is a hydrogen bond between the constitutional repeating units of poly-(N-vinylpyrrolidone) and polypyrrole. It was determined that the size of the particles of the disperse phase decreases with the increase of poly-(N-vinylpyrrolidone) molecular weight. It was also determined that the size of particles increases with the increase of the mass fraction of polypyrrole aqueous suspension. It was shown that the disperse phase particles are rod-like, and the increase of molecular weight of poly-(N-vinylpyrrolidone) in an aqueous solution results in additional lengthwise stretching of particles. It was also shown that the viscosity of the stabilized poly-(N-vinylpyrrolidone) aqueous suspension follows the Einstein law.